Utilization of Pseudomonas fluorescens as Antimicrobial agent on Lipolysis Inhibitition of Rice Bran - Widiyastuti, Titin; Prayitno, Caribu Hadi; Munasik, Munasik (ANIMAL PRODUCTION, 2002)
Feedstuff was limited by fat content, certainly, if the material feedstuff was storage on long time periods. Fat was oxidized or hydrolyzed, which was decreased nutritional quality. A Research on Inhibited ofÂ  Lypolysis Rice Bran with anti-microbial compound of Pseudomonas fluorescens was conducted during ten month. The research used experiment methods, with Randomized Completely Block Design, storage as block and concentration of anti-mikrobial compound as treatment. Fat and polyunsaturated fatty acids content during storage was observed. Result of experiment showed anti-microbial compound inhibited oxidize and hydrolyze process of fat rice bran during six month storage. (Animal Production 4(2): 89-93 (2002)Â